Ear and skull base paraganglioma: review of literature - D. Abdrakhmanova; K. Niemczyk; A. Mustafin; G. Mukhamadieva; N. Papulova (Medičnì Perspektivi, 2024)
The actuality of the research is determined by the lack of systemized information on the ear and skull base paraganglioma. Currently, from 500 to 1000 cases of paraganglioma or pheochromocyte are diagnosed in the United States of America annually. The combined morbidity of benign tumor forms is evaluated to be between 0.7 to 1.0 for 100000 people per year. Even though the results in understanding the nature of paraganglioma, as well as treatment thereof, are successful, the amount of literature on this topic only increases. The research aims to analyze study of the terminology, classification, diagnostics, and treatment of paraganglioma. Special attention was brought to the preoperative preparation and embolization of vessels, which supply blood to the tumor as well as to the problem of repeated bouts of glomangioma. The objective of the research is the selection of relative sources, argumentation analysis, and material systematization. For the analysis, 53 research articles were included. During the compilation of this study, such methods, as analysis, synthesis, information collection and systematization, and generalization, were used. In this article, various paraganglioma classifications, endoscopic treatment methods, other aspects of paraganglioma therapy, and diagnosis and treatment thereof, were presented. More and more researchers recommend individual and adapted approaches for each case with the inclusion of factors, related to the patient, including age, treatment goals, other infections, gene status, anatomical issues, caused by the tumor growth, its sizes, and other factors. This literature review focuses on ear and skull base paragangliomas, rare, usually benign, hyper-vascularized neuroendocrine tumors often treated surgically. Alternative treatments like cyber-knife, gamma-knife, and endoscopic approaches are also discussed, highlighting their efficacy for specific cases. The study emphasizes individualized treatment plans considering patient-specific factors, with stereotactic radiosurgery being a safe and effective option for many patients. Materials of the research can be used by doctors of various specializations to enrich their knowledge and for further study of paragangliomas of various localizations.